Analisis Yuridis Penegakan Hukum Terhadap Warga Negara Asing Sebagai Pelaku Tindak Pidana Keimigrasian - Taekedangan, Fahrul Resa; Wattimena, Josina Augustina Yvonne; Supusepa, Reimon (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Immigration as stated in Chapter 1 Article 1 number (1) of Law Number 6 of 2011 concerning Immigration is a matter regarding the movement of people entering or leaving the territory of the Republic of Indonesia and the supervision of foreigners in the territory of the Republic of Indonesia. The arrival of foreign nationals can actually have a positive impact, as in this era of globalization it can help develop tourism levels and develop economic investment in various regions. However, many people do not know that crimes often occur when foreign nationals come to Indonesia, for this reason the problem studied in this paper is how to overcome immigration crimes committed by foreign nationals.Results of the Research: Efforts to overcome immigration crimes committed by foreign citizens by means of prevention and deterrence. Prevention is a temporary prohibition on certain people leaving the territory of Indonesia for certain reasons. Meanwhile, deterrence is a temporary prohibition on certain people from entering Indonesian territory based on certain reasons. The implementation of prevention and deterrence is the authority of the Ministry of Law and Human Rights issued through the Directorate General of Immigration. There is a need for the government and law enforcement officials to play a role in preventing and dealing with immigration crimes committed by foreign citizens.